2021
DOI: 10.1002/ange.202113077
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Selectivity and Stability of Finned Ferrierite Catalysts in Butene Isomerization

Abstract: Designing zeolite catalysts with improved mass transport properties is crucial for restrictive networks of either one-or two-dimensional pore topologies. Here, we demonstrate the synthesis of finned ferrierite (FER), a commercial zeolite with two-dimensional pores, where protrusions on crystal surfaces behave as pseudo nanoparticles. Catalytic tests of 1-butene isomerization reveal a 3-fold enhancement of catalyst lifetime and an increase of 12 % selectivity to isobutene for finned samples compared to correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…Alternatively, solids extracted from the identical growth mixture without seeds are a non-zeolite crystalline phase (Figure S5). It is possible that the rough protrusions have an FAU crystal structure, analogous to finned zeolites where the fins grow epitaxially on surfaces of zeolite seeds. , Conversely, these features may be defects with a similar (unidentified) structure as the non-seeded synthesis. It is apparent, however, that growth of the FAU crystal substrate is highly dependent upon the Si/Al ratio of the growth medium.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, solids extracted from the identical growth mixture without seeds are a non-zeolite crystalline phase (Figure S5). It is possible that the rough protrusions have an FAU crystal structure, analogous to finned zeolites where the fins grow epitaxially on surfaces of zeolite seeds. , Conversely, these features may be defects with a similar (unidentified) structure as the non-seeded synthesis. It is apparent, however, that growth of the FAU crystal substrate is highly dependent upon the Si/Al ratio of the growth medium.…”
Section: Resultsmentioning
confidence: 99%
“…The same procedure was performed for the as-synthesized Core sample as a reference using a protocol similar to the preparation of finned zeolites. [27] We first tested the annealing process on the Core, which involves the suspension of zeolite crystals in an alkaline solution (pH 11) containing a small quantity of silica (close to the solubility of zeolite beta) and an organic structure-directing agent (tetraethylammonium, TEA). This solution was hydrothermally treated at 170 °C for different times.…”
Section: Resultsmentioning
confidence: 99%
“…Additional acid site characterization using pyridine-FT-IR revealed that Core, CS, and CSA samples have an approximate 70 : 30 split between Brønsted acid sites (BAS) and Lewis acid sites (LAS), whereas CA has slightly higher BAS density (76 %). Solid state 27 Al NMR analysis reveals that the percentage of extra-framework Al (EFAl) falls within a narrow range for all samples (10-12 %), with the exception of CS that has a slightly higher EFAl content (ca. 19 %).…”
Section: Samplementioning
confidence: 99%